Neurodegeneration and the Circadian Clock - Hood, Suzanne; Amir, Shimon (Frontiers in Aging Neuroscience, 2017)
Despite varied etiologies and symptoms, several neurodegenerative diseases – specifically, Alzheimer’s, Parkinson’s, and Huntington’s diseases – share the common feature of abnormal circadian rhythms, such as those in behavior (e.g., disrupted sleep/wake cycles), physiological processes (e.g., diminished hormone release), and biochemical activities (e.g., antioxidant production). Circadian disturbances are among the earliest symptoms of these diseases, and the molecular mechanisms of the circadian system are suspected to play a pivotal, and possibly causal, role in their natural histories. Here, we review the common circadian abnormalities observed in Alzheimer’s, Parkinson’s, and Huntington’s diseases, and summarize the evidence that the molecular circadian clockwork directly influences the course of these disease states. On the basis of this research, we explore several circadian-oriented interventions proposed as treatments for these neurological disorders.